2022
DOI: 10.3390/foods11244117
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Variability in the Thermal Resistance (D-Values) of Food-Borne Pathogens—A Challenge for Thermal Validation Trials

Abstract: The thermal processing of food relies heavily on determining the right time and temperature regime required to inactivate bacterial contaminants to an acceptable limit. To design a thermal processing regime with an accurate time and temperature combination, the D-values of targeted microorganisms are either referred to or estimated. The D-value is the time required at a given temperature to reduce the bacterial population by 90%. The D-value can vary depending on various factors such as the food matrix, the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 126 publications
0
8
0
Order By: Relevance
“…The survivors are typically determined by linear and Weibull mathematical models, which can thereby predict the outcome/effect of any processing treatment using heat on the inactivation of these bacteria (Forghani et al, 2018). A review by Soni et al (2022b) indicated the variability in D values reported in literature, wherein there are serval factors that contribute to their resistance. However, at times the mechanism is not acquired but is inherited.…”
Section: Lhr In E Colimentioning
confidence: 99%
See 4 more Smart Citations
“…The survivors are typically determined by linear and Weibull mathematical models, which can thereby predict the outcome/effect of any processing treatment using heat on the inactivation of these bacteria (Forghani et al, 2018). A review by Soni et al (2022b) indicated the variability in D values reported in literature, wherein there are serval factors that contribute to their resistance. However, at times the mechanism is not acquired but is inherited.…”
Section: Lhr In E Colimentioning
confidence: 99%
“…A review by Soni et al. (2022b) indicated the variability in D values reported in literature, wherein there are serval factors that contribute to their resistance. However, at times the mechanism is not acquired but is inherited.…”
Section: Lhr In E Colimentioning
confidence: 99%
See 3 more Smart Citations